Genotypes at the GluR6 Kainate Receptor Locus are Associated with Variation in the Age of Onset of Huntington Disease - Rubinsztein, David C.; Leggo, Jayne; Chiano, Mathias; Dodge, Alan; Norbury, Gail; Rosser, Elisabeth; Craufurd, David (Proceedings of the National Academy of Sciences - PNAS, 1997)
Huntington disease (HD) is associated with abnormal expansions of a CAG repeat close to the 5′end of the IT15 gene. We have assembled a set of 293 HD subjects whose ages of onset were known and sized their HD CAG repeats. These repeats accounted for 69% of the variance of age of onset when we used the most parsimonious model, which relates the logarithm of age of onset to a function of CAG repeat number. Since other familial factors have been proposed to influence the age of onset of HD, we have examined a number of candidate loci. The CAG repeat number on normal chromosomes, the Δ 2642 polymorphism in the HD gene, and apolipoprotein E genotypes did not affect the age of onset of HD. Although mitochondrial energy production defects in HD have led to suggestions that variants in the mitochondrial genome may be associated with clinical variability in HD, this suggestion was not supported by our preliminary experiments that examined the DdeI mitochondrial restriction fragment length polymorphism at position 10,394. Excitotoxicity has been a favored mechanism to explain the cell death in HD, particularly since intrastriatal injection of excitatory amino acids in animals creates HD-like pathology. Accordingly, we investigated the GluR6 kainate receptor. Of the variance in the age of onset of HD that was not accounted for by the CAG repeats, 13% could be attributed to GluR6 genotype variation. These data implicate GluR6-mediated excitotoxicity in the pathogenesis of HD and highlight the potential importance of this process in other polyglutamine repeat expansion diseases.